2007
DOI: 10.1038/sj.ki.5002160
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular hyperfiltration: A new marker of metabolic risk

Abstract: Chronic kidney disease coexists with metabolic syndrome and this relationship may be apparent before overt manifestations of cardiovascular disease. To investigate early stages of the natural history of associations between renal function and metabolic syndrome, we phenotyped 1572 young (mean age=18.4 years), apparently healthy men for metabolic risk factors and estimated their creatinine clearance based on the Cockcroft-Gault equation. High metabolic risk (clustering of at least three metabolic risk factors) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
166
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(186 citation statements)
references
References 34 publications
15
166
1
4
Order By: Relevance
“…Many studies investigated that BMI and blood pressure was associated with glomerular lesions in ORG patients [5,6,17,18]. In hypertensive patients, increasing renal tubular sodium reabsouption and glomerular hyperfiltration may cause glomerulomegaly [1].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies investigated that BMI and blood pressure was associated with glomerular lesions in ORG patients [5,6,17,18]. In hypertensive patients, increasing renal tubular sodium reabsouption and glomerular hyperfiltration may cause glomerulomegaly [1].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been claimed that the metabolic syndrome is associated with hyperfiltration, as estimated by the Cockcroft-Gault formula [33]. However, GFR estimates by the Cockcroft-Gault formula may be spuriously elevated in obese participants.…”
Section: Hyperfiltration Independent Of Diabetesmentioning
confidence: 99%
“…18 The proposed mechanisms to explain renal damage induced by MetS are hyperfiltration, proinflammatory and prothrombotic state, endothelial dysfunction, and oxidative stress. 12,13,19,20 To circumvent these issues, MetS had been identified as initiating factor of CKD and had the impact on renal function progression in diabetic or nondiabetic early-stage CKD. 6,8,16 A sizeable study utilizing data from the Atherosclerosis Risk in Communities cohort confirmed a step-wise increase with the risk of developing CKD, each MetS criterion met by non-diabetic adults, even after putting in place prophylactic measures for the possible development of diabetes mellitus and hypertension.…”
Section: Discussionmentioning
confidence: 99%